Coronary Anomalies in 11, 267 Southwest Chinese Patients Determined by Angiography. (19th February 2021) - Jiang, Xin; Zhou, Ping; Wen, Chunlan; Yin, Zhao; Liu, Tao; Xu, Meiling; Yang, Chengming; Wang, Hongyong; Song, Wenxing; Fang, Yuqiang; Zeng, Chunyu
Abstract : Background . The prevalence of coronary artery anomalies (CAAs) is rare and varies among different countries or areas. More importantly, the symptoms exhibited by some CAAs make the diagnosis of coronary artery disease (CAD) difficult and hamper the physician from making the right intervention for CAD patients. Objective . To investigate the prevalence of CAAs in 11, 267 patients from three hospitals in Southwest China. Methods . 11, 267 patients who have undergone coronary angiography from three Southwest China hospitals were investigated retrospectively. Dominance patterns, prevalence, and the location of each CAA were recorded and analyzed. Results . The presence of a dominant right coronary artery (RCA) was found in 60.58% of patients. CAAs were found in 11.12% (1258) patients, and 87.66% anomalies were located in the left anterior descending (LAD) artery and its branches. Most of CAAs were found to be myocardial bridges (MBs, 1060 cases, 9.41%). Other CAAs included anomalous coronary origin (43 cases, 0.38%), coronary artery fistulas (CAFs, 36 cases, 0.32%), and coronary artery aneurysm or ectasia (119 cases, 1.06%). It also noted that most anomalies were found with RCA originating from the left coronary sinus (79.07%), most CAFs were located in the LAD and its branches (58.33%), and most coronary artery ectasias were located in the RCA (43.25%). Conclusions . CAAs in patients from Southwest China were unique compared to other studies. Recognition of these CAAs is important for accurate diagnosis and treatment choice of patients with chest pain.